A multi-disciplinary, protocolised care for hip fracture surgeries shortens hospital stay, time to admission and surgery - Khai Cheong Wong; Gideon Jia Wei Cheok; Kenny Xian Khing Tay; Joyce Suang Bee Koh; Tet Sen Howe; Yeong Huei Ng (Proceedings of Singapore Healthcare)
Background Our institution implemented a multi-disciplinary protocolised care for surgically managed hip fractures in 2017, initiating measures pre-operatively to provide early access to surgery, and post-operatively to ensure early mobilisation and smooth transition to step down care. Objectives Key performance indicators (time to admission and time to surgery) and acute outcomes (length of stay, discharge disposition and inpatient mortality) were evaluated to determine the impact of multi-disciplinary protocolised care on surgically managed hip fracture patients. Methods 935 patients in the POST-PROTOCOL group (between February 2017 to January 2020) were compared with 701 patients in the PRE-PROTOCOL group (between January 2015 to January 2017) in terms of key performance indicators and acute outcomes. Results In the POST-PROTOCOL group, a higher proportion were of ASA class III and IV ( p = .026). More patients in the POST-PROTOCOL group were admitted to the ward within 4 hours (97.2% vs 86.0%; p < .001) and operated on within 48 hours (56.4% vs 36.8%; p < .001). Mean length of stay was shorter in the POST-PROTOCOL group (11.2 ± 9.0 vs 14.8 ± 13.0 days; 95% CI, 2.5 to 4.7; p < .001), with more patients discharged within 9 days (55.6% vs 43.2%; p < .001). Inpatient mortality rate was similar ( p = .213). Conclusion Despite having a higher proportion of patients with poorer physiological status, time to admission, time to surgery and length of stay improved in the POST-PROTOCOL group.